Measurement of Platelet Function in an Experimental Stroke Model With Aspirin and Clopidogrel Treatment - Lieschke, Franziska; Zheng, Yi; Schaefer, Jan Hendrik; van Leyen, Klaus; Foerch, Christian (Frontiers in Neurology, 2020)
Dual antiplatelet treatment (DAPT) increases the risk of tPA-associated hemorrhagic transformation (HT) in ischemic stroke. To investigate the effects of DAPT in rodents, reliable indicators of platelet function utilizing a minimally invasive procedure are required. We here established a fluorescence-based assay to monitor DAPT efficiency in a mouse model of ischemic stroke with HT. Male C57/BL6 mice were fed with aspirin and clopidogrel (ASA+CPG). Venous blood was collected, stimulated with thrombin, labeled with anti-CD41-FITC and anti-CD62P-PE, and analyzed by flow cytometry. Subsequently, animals were subjected to experimental stroke and tail bleeding tests. HT was quantified using NIH ImageJ software. In ASA+CPG mice, the platelet activation marker CD62P was reduced by 40.6±4.2% (p<0.0001) compared to controls. In vitro platelet function correlated inversely with tail bleeding tests (r=-0.8, p=0.0033, n=12). 24h after drug withdrawal, platelet activation rates in ASA+CPG mice were still reduced by 20.2±4.1% (p=0.0026) compared to controls, while tail bleeding volumes were increased by 4.0±1.4µl (p=0.004). Conventional tests using light transmission aggregometry require large amounts of blood and thus cannot be used in experimental stroke studies. In contrast, flow cytometry is a highly sensitive method that utilizes small volumes and can easily be incorporated into the experimental stroke workflow. Our test can be used to monitor the inhibitory effects of DAPT in mice. Reduced platelet activation is indicative of an increased risk for tPA-associated cerebral hemorrhage following experimental stroke. The test can be applied to individual animals and implemented flexibly prior and subsequent to experimental stroke.